ANALISIS PENGARUH FINANCIAL DISTRESS, UKURAN PERUSAHAAN, SOLVABILITAS, DAN PROFITABILITAS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Listantri, Ferni; Mudjiyanti, Rina (Media Ekonomi, 2016)
The purpose of the research was to find the empirical evidence of the financial distress positive effect to the going concern opinion audit, to find the empirical evidence of the negative effect of company to the going concern opinion audit, to find empirical evidence of solvability’s positive effect to the going concern opinion audit, to find empirical evidence of profitability’s negative effect to the going concern opinion audit.This research is descriptive quantitative research where the analysis was conducted using logistic regression. Then type of data used in the research wassecondary data, the population and sample which used in this research was 100 of companies. Result of the research shows that financial distress partially does not positively affect to the going concern opinion audit, size of the company does not affect negatively to going concern opinion audit, the solvability positively affect to the going concern opinion audit, and profitability negatively affects to the going concern opinion audit.Keywords : going concern opinion audit, financial distress, size of company,solvability, and profitability.